Sediment routing system and sink preservation during the post-orogenic evolution of a retro-foreland basin: The case example of the North Pyrenean (Aquitaine, Bay of Biscay) Basins. (February 2020) - Ortiz, Alexandre; Guillocheau, François; Lasseur, Eric; Briais, Justine; Robin, Cécile; Serrano, Olivier; Fillon, Charlotte
Abstract: We investigated here the evolution of the sediment routing system, i.e. the sediment transport and deposition evolution along successive depositional topographies and environments, and the sink (i.e. deposited sediments) preservation in a foreland basin from the period of mountain belt shortening to its post-orogenic stage. The studied system is the North Pyrenean retro-foreland basin from 50 Ma to today which is, composed of a subsiding platform (the Aquitaine Basin) fed by the erosion of the Pyrenees passing laterally to a slope and a deep-sea plain (the Bay of Biscay deep basin), the ultimate area of deposition. This study is based on a double seismic stratigraphic and structural analysis of an extensive seismic dataset and on an age model of the sediments combining biostratigraphy, orbitostratigraphy and sequence stratigraphy with a time resolution of 0.1 Ma. Four major periods of deformation corresponding to a single or a set of stratigraphic sequence boundaries were characterized. The Pyrenean shortening decrease may be recorded by a basin-scale uplift at 49.8 Ma (Late Ypresian). The paroxysm of the piggy-back shortening and related uplift is dated at 35.8 Ma (Priabonian). The end of the Pyrenees shortening (transition to post-orogenic conditions) is well dated between 27.1 and 25.2 Ma (Chattian). A major West European scale deformation of possible mantle origin uplifted the basin from 16.4 to 10.6 Ma (Late Burdigalian to Early Tortonian). These major periods of deformations controlled the sink preservation at the first order through the ratio between the accommodation space created by subsidence on the Aquitaine platform (Asub ) and the siliciclastic sediment supply coming from the erosion of the Pyrenees (Ssc ). A general model is proposed. At the time of the foreland basin when ΔAsub ≤ ΔSsc, most of the sediments are preserved on the platform as a progradational-aggradational wedge (up to 25.2 Ma here). At the time of the post-foreland evolution when ΔAsub < ΔSsc, most of the sediments are transferred to the deep-sea plain with few preservations on the platform and when ΔAsub ≪ ΔSsc with ΔAsub ≤ 0, all of the sediments are transferred to the deep-sea plain as deep-sea fans and fluvial by-pass or erosion is the dominant process on the platform. The continental sediment routing system is mainly provided along nearly flat alluvial plains with extensive lakes and/or humid zones, i.e. the local base levels of the alluvial fans. The Aquitaine retro-foreland was never overfilled. Graphical abstract: Image 1 Highlights: A new chronostratigraphic and sequence stratigraphic framework. Characterization of successive deformations: age, wavelengths, causes. Evolution of the sediment routing system: depositional profiles and topographies. A sink preservation model based on the ratio vertical movements/sediment supply.